2009
DOI: 10.1021/ja809617v
|View full text |Cite
|
Sign up to set email alerts
|

Zwitterionic Polymerization: A Kinetic Strategy for the Controlled Synthesis of Cyclic Polylactide

Abstract: The zwitterionic ring-opening polymerization of lactide initiated by N-heterocyclic carbenes generates cyclic polylactides with well-defined molecular weights between M(n) = 5000 and 30,000 g/mol with narrow polydispersities (M(w)/M(n) < or = 1.31). These zwitterionic polymerizations are extremely rapid (k(p) = 48.7 M(-1) s(-1)), but also exhibit exceptional control of molecular weight and molecular weight distribution. The unusual kinetic features of these zwitterionic polymerizations are illuminated with kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
212
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 202 publications
(228 citation statements)
references
References 43 publications
15
212
0
Order By: Relevance
“…Similar behavior was observed for the zwitterionic ring-opening polymerization of lactones 1,16,20−22 and is attributed to a slow rate of initiation relative to propagation. 20,22 This is also evident in the kinetic behavior, where an induction period is observed followed by a first order disappearance of monomer ( Figures S6 and S7, Supporting Information).The cyclic structure of the PLA generated from isothioureas 1 and 2 was inferred by a combination of 1 H NMR spectroscopy, MALDI-TOF mass spectrometry, and dilute solution viscosity measurements. The 1 H NMR spectra of the PLA shows no observable end groups ( Figure S1).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Similar behavior was observed for the zwitterionic ring-opening polymerization of lactones 1,16,20−22 and is attributed to a slow rate of initiation relative to propagation. 20,22 This is also evident in the kinetic behavior, where an induction period is observed followed by a first order disappearance of monomer ( Figures S6 and S7, Supporting Information).The cyclic structure of the PLA generated from isothioureas 1 and 2 was inferred by a combination of 1 H NMR spectroscopy, MALDI-TOF mass spectrometry, and dilute solution viscosity measurements. The 1 H NMR spectra of the PLA shows no observable end groups ( Figure S1).…”
mentioning
confidence: 67%
“…1,4,20,21 The ZROP of lactide with N-heterocyclic carbenes is rapid (minutes), but molecular weights >30 kDa are difficult to obtain. 16,22,23 We recently reported that the amidine 1,8-diazabicyclo- [5.4.0]undec-7-ene (DBU) was sufficiently nucleophilic to mediate the ZROP of lactide to generate cyclic polylactides but was accompanied by the cogeneration of linear polylactides. 11 We had proposed that the linear polylactides might arise from competitive deprotonation of the amidininium zwitterion to generate the neutral ketene aminal (KA, Scheme 2).…”
mentioning
confidence: 99%
“…The authors recently demonstrated 8 the synthesis of high-molecular weight cyclic poly(e-caprolactone) (as high as 114k) with polydispersities in most cases above 1.7. The kinetic data suggest that the carbene initiator was much less reactive for poly(e-caprolactone) than for polylactide, and strongly suggests based on the kinetic mechanism proposed 96 that about 3% of initiator is consumed or bound to the polymer at 50% conversion.…”
Section: Ring-expansion Polymerizationsmentioning
confidence: 85%
“…The kinetic mechanism for this polymerization is given in Scheme 8 based on a kinetic analysis and Monte Carlo simulations. 96 For the low polydispersities found, the initiation rate coefficient, k i , must be relatively high and much greater than ring closure, k c . The simulations SCHEME 4 Various multicyclic-and linear-cyclic copolymer topologies constructed by the ESA-CF process.…”
Section: Ring-expansion Polymerizationsmentioning
confidence: 92%
“…Kinetic studies of the ZROP of lactide with IMes demonstrated that the formation of the initial zwitterion Z 1 (initiation) was slower than addition of monomer to growing zwitterions Z n . Experimental studies indicated that the rate of polymerization as well as the molecular weights and molecular weight distributions of the resulting cyclic polyesters are a complicated function of the rates of initiation, propagation, and cyclization, 12 but the influence of the nucleophile or electrophile on these relative rates is not yet clear.…”
Section: ■ Introductionmentioning
confidence: 99%